2020
DOI: 10.3389/fmicb.2020.588099
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Metabolism Impairment via Single Gene Mutation in the glgBXCAP Operon Alters the Survival Rate of Escherichia coli Under Various Environmental Stresses

Abstract: Glycogen is a highly branched polysaccharide that is widely present in all life domains. It has been identified in many bacterial species and functions as an important energy storage compound. In addition, it plays important roles in bacterial transmission, pathogenicity, and environmental viability. There are five essential enzymes (coding genes) directly involved in bacterial glycogen metabolism, which forms a single operon glgBXCAP with a suboperonic promoter in glgC gene in Escherichia coli. Currently, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 46 publications
(93 reference statements)
5
25
0
Order By: Relevance
“…As for short-term adaptation, Biselli et al discovered that E. coli tended to decrease growth and maintenance rate in exchange of longer survival during carbon deficiency (Biselli et al, 2020). In this study, we examined the response of E. coli BW25113 to nutrient fluctuation, according to which, higher glucose concentration (0.8%) significantly improved the number of viable cells during 24-h culture (Figure 1A), which is consistent with previous studies (Wang et al, 2018(Wang et al, , 2020b. Bacterial replication is a key factor for host colonization, resource exploitation, and between-host transmission (Rohmer et al, 2011), high rate of which could contribute to bacterial virulence.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…As for short-term adaptation, Biselli et al discovered that E. coli tended to decrease growth and maintenance rate in exchange of longer survival during carbon deficiency (Biselli et al, 2020). In this study, we examined the response of E. coli BW25113 to nutrient fluctuation, according to which, higher glucose concentration (0.8%) significantly improved the number of viable cells during 24-h culture (Figure 1A), which is consistent with previous studies (Wang et al, 2018(Wang et al, , 2020b. Bacterial replication is a key factor for host colonization, resource exploitation, and between-host transmission (Rohmer et al, 2011), high rate of which could contribute to bacterial virulence.…”
Section: Discussionsupporting
confidence: 87%
“…For glucose concentration, 1 × M9 minimal medium supplemented with higher level of glucose (0.8%) showed the highest number of viable cells in the culture, which was significantly different from those with 0.2% and 0.4% glucose (P-value <0.05) after culturing for 20 h (Figure 2A). This result is similar with previous studies performed on E. coli BL21(DE3) and E. coli DH5α, which confirms that high level of carbon source facilitates the replication of bacterial cells (Wang et al, 2018(Wang et al, , 2020b. As for osmotic stress, four sodium chloride (NaCl) concentrations (0, 1, 3.5, and 5%) were explored and statistical analysis showed that the number of viable cells in LB broth supplemented with 0% NaCl at 24 h is significantly higher than other tested groups, that is, LB broth supplemented with 1%, 3.5%, and 5% NaCl (Figure 2B).…”
Section: Bacterial Growthsupporting
confidence: 92%
See 2 more Smart Citations
“…It has been reported that most bacteria accumulate glycogen in stationary phase when nitrogen source is limited while carbon source is abundant ( Wilson et al, 2010 ; Wang and Wise, 2011 ). However, through comparative analysis of glycogen content curves, it was noticed that glycogen metabolism in Escherichia coli had two stages, synthesis stage and degradation stage ( Strydom et al, 2017 ; Wang et al, 2020c ), which could be used to study the structural alteration of glycogen α particles. By using E. coli BL21(DE3) as a model organism, we recently revealed that glycogen α particles in bacteria followed a similar pattern of structural change as in healthy liver, that is, fragile during synthesis stage and stable during degradation stage ( Wang M. et al, 2021 ); in addition, fragile glycogen particles tend to have longer chain length distribution than stable glycogen particles ( Wang M. et al, 2021 ), which is also consistent with previous results in healthy and diabetic mice ( Hu et al, 2018 ).…”
Section: Glycogen α Particlesmentioning
confidence: 99%